Essence of architecture engineering and its abilities - Daneshgar, Davood (2008)
In developing societies, architecture express as an art, only a science or profession, therefore researcher attempts to analyze the relation between building technology and aesthetics by regarding to essential study on the old construction (building) and global architecture appearances. Likewise according to ability of management, creative and talents rate, knowledge of experiential-academic architects and civil engineers, conclusion are saying that architecture is a mainly joint of art, science and profession in cooperation with civil engineering. Buildings and engineering constructions can theoretically be separated, but practically less and less.